Junior Secondary Basic Science performance as Predictor of Senior Secondary Biology performance in Public Secondary Schools In Portharcourt Metropolis - Allwell Sunny Njigwum; Dr. Ibiene T. Longjohn (African Journal of Behavioural and Scale Development Research, 2019)
The study investigated if Junior School Certificate Examination (JSCE) results in Basic Science would Predict Senior School Certificate Examination (SSCE) results in Biology in public secondary schools in Port Harcourt Metropolis. The study employed both ex-post facto and correlation designs. A sample of 593 students ( 303 males and 290 females) was used for the study. Purposive sampling technique was used to select the sample (made up of only students who sat for 2011 JSCE and 2014 SSCE in public schools in Port Harcourt Metropolis of Rivers State). Three hypotheses were tested at .05 level of significance. Data was collected using students Grade chart (SGC) Inventory form. Data was analysed using simple regression analysis. The findings of the study showed that JSCE Basic Science is not a potent predictor of SSCE Biology performance (β = 0.030, P > .05). Also, gender of students who took the JSCE Basic Science had no significant prediction on SSCE Biology performance (Female β = -0.016, P > .05; Male β = 0.066, P > .05). It was recommended that JSCE Basic Science curriculum be reviewed to be in conformity with the SSCE syllabus for science subjects (Biology) in order to enhance its predictive validity.